Has the credit supply shock asymmetric effects on macroeconomic variables? - Valentina Colombo; Alessia Paccagnini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
We investigate the role played by the credit supply shock across the business cycle in the U.S. over the period 1973 - 2018. We estimate a nonlinear VAR including nominal, real, monetary, and financial variables. According to our results, a credit supply shock triggers asymmetric and negative effects on macroeconomic variables. We find that the state-dependent forecast error variance decomposition of industrial production, employment, and inflation due to the shock is from six to eight times larger in recessions than in normal times.
Keywords: C32; E32; E52; 330; Credit supply shock; Smooth Transition VAR; Nonlinearities